Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Maulana Habibie, Rosyid; Muh. Hasyim Rosyidi; Munawwaroh (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
As a leader in an educational institution, a school principal has a great influence on the institution and also the community within the institution. The essence of transformation is changing potential into real energy. School principals who are able to carry out leadership transformations mean they can change the potential of their institution into energy to improve the performance of existing teachers. Transformational leadership is described as a leadership style that can arouse or motivate employees, so that they can develop and achieve performance at a high level, beyond what they previously expected. Transformational leadership in principle motivates subordinates to do better than what they can do, in other words it can increase subordinates' trust or self-confidence which will have an effect on improving performance